The Effect of Gross Profit, Operational Profit and Net Profit on Future Cash Flows - Mudjiyono Mudjiyono; Dimas Adi Wicaksono (Soegijapranata Catholic University, 2022)
This study aims to find empirical evidence about the effect of gross profit, operating profit, and net profit on cash flow of future operating activities in manufacturing companies listed on the Indonesia Stock Exchange in the period of 2016-2019. The method used to select the subject of this research is purposive sampling. The data were tested using multiple linear regression at a significance level of 5% with the help of the SPSS program. Based on the results of the partial test (t test), operating income and net income have significant effect in predicting the cash flows of operating activities in the future, while gross profit has no significant effect on predicting the cash flows of operating activities in the future. Meanwhile, based on the simultaneous test (F test), gross profit, operating profit, and net profit simultaneously have significant effect in predicting the cash flow of operating activities in the future.